The Archaeology of Sectarianism: Ritual, Resistance and Hierarchy in Kh. Qumran - Regev, Eyal 1970- (2009)
The archeological record from kh. Qumran is examined without regard to the scrolls in order to understand the ‘ideology' of the inhabitants and whether they can be defined as a sect. The enormous quantity of tableware indicates ritualization of meals to the exclusion of others (implying strong social boundaries), a practice that is common among elite groups. Resistance is manifested in the animal bone deposits which attest to meat consumption as a sacred ritual. Resistance is also expressed by the distinctive and identical mode of burial. Social hierarchy and ritualization are indicated by ritual baths with multiple partitions. Several rings may also indicate the presence of women. In conclusion, the rituals and resistance are consistent with sectarian ideology. The connection between the inhabitants of kh. Qumran and the Yaḥad sect is probable, although not necessarily direct.\n4207 \n4207